Evolution of municipal law in 2014-2016. - Y. Blagov (Правоприменение, 2017)
УДК 342The subject. This article is devoted the municipal reform 2014-2016. The reform of state are institutes of territorial organization, organizational principles, competency bases of local self-government.The purpose of this paper is to show that the municipal reform 2014-2016 is directed on limiting local self-government and the subordination of local self-government to state authorities of the subjects of Russia.Methodology. The author uses a dialectical method, a method of analysis and synthesis, a formal legal method, a comparative legal method.Results, scope. Urban districts with intracity and intercity division areas – two new municipalities have been legally introduced. In science municipal law formed two points of view on the admissibility and feasibility of separating the urban district in the inner city areas. According to the first point of view, the separation of large urban districts in the inner city areas is acceptable and appropriate. According to the second point of view, the separation of large urban districts in the inner city areas is unacceptable and inappropriate. The author adheres to the second point of view, since the introduction of a two-tier model of local government organization would violate the principle of unity of municipal economy, will lead to the rupture of a single urban space on the organizational and financial sustainability areas dependent city district, will lead to a sharp increase in the number of deputies and municipal employees, unnecessary increase financial expenses.Municipal and regulatory policy in the sphere of organizational principles of local self-government is aimed at the maximum limit of direct elections of the population of the local self-government, which leads to their further alienation from the local authorities (the direct election of saved only 11 urban districts (13 %), which are the administrative centers of the subject of the Russian Federation). In addition, the actual subject of the Russian Federation determines the organizational model of local self-government for all the municipalities in its territory. This contradicts the Russian Constitution and the European Charter of Local Self-Government.Federal Law No. 136-FZ of the legislation on local government introduced a completely new institution – the redistribution of powers. In accordance with pt. 1.2 of Article 17 of the Federal Law No. 131-FZ of the laws of the Russian Federation subject may be a redistribution of powers between the local authorities and public authorities of the RF subject. The norms of the Constitution there is no reference to the possibility of transmission to public authorities of powers of local governments to address local issues. From the analysis of the norms of the Constitution, the European Charter of Local Self-Government, the legal posi-tion of the Constitutional Court is apparent that the public authorities as a general rule is not entitled to decide local issues, to withdraw from the jurisdiction of the powers of local government. Meanwhile, as of March 1, 2017 34 subjects of the Russian Federation adopted laws on the redistribution of powers between the local authorities and public authorities of the Russian Federation.The results of the study can be applied in the design of the legal regulation of Institute of territorial organization of local self-government; Institute organizational principles of local self-government; Institute of competency bases of local self-government.Conclusions. Analyzing the latest evolution of municipal law the author comes to the conclusion that the target of the municipal reform 2014-2016 proclaimed by the legislator – the restoration of the lost connection between citizens and local self-governments – is clearly declarative in nature. The real target of the reform is a gradual, but consistent inte-gration of local self-government into the system of public authorities.